PENELUSURAN PERANAN SUMBER-SUMBER PENDAPATAN DAN FISCALL STRESS TERHADAP DERAJAT DESENTRALISASI FISKAL KABUPATEN/KOTA DI PROVINSI JAWA TENGAH 2007-2011 - Kartika, Fitria Yuliani; Masdjojo, Gregorius Nasiansenus (Jurnal Ilmiah Telaah Manajemen, 2014)
This study aimed to examine the effect of Local Revenue, the General Allocation Fund, the Special Allocation Fund and the Fiscall Stress on Fiscal Decentralization Degree of Regency/City in Central Java province on 2007-2011. The data used is Realized Budget Report of 35 district and city in the province of Central Java. Types of data used is a combination of time series and cross section data. Data is analyzed by panel regression technique. The results showed that the Local Revenue has positive and significant impact on Fiscal Decentralization Degree, the General Allocation Fundhas negative and significant impact on Fiscal Decentralization Degree,the Special Allocation Fund has negative and significant impact on Fiscal Decentralization Degree, FiscallStress has positive and significant impact on Fiscal Decentralization Degree. Keywords: The Fiscal Decentralization Degree, The Local Revenue, The General Allocation Fund, The Special Allocation Fund, The Fiscall Stress.